Exploring unknown life stages of Arctic Tanytarsini (Diptera: Chironomidae) with DNA barcoding - Stur, Elisabeth; Ekrem, Torbjørn (Zootaxa, 2011)
We present the first results from a project on Spitsbergen and Bear Island where the ultimate goal is to provide genetic and morphological identification keys to all species. Five Tanytarsini species have been recorded from Svalbard. By sequencing partial COI gene sequences, we have associated larvae of all of these, and describe the hitherto undescribed larval stages of Microspectra insignilobus Kieffer, M. radialis Goetghebuer and Tanytarsus heliomesonyctios Langton. We also present keys to larva, pupa and imagines of all Tanytarsini species found on Svalbard and discuss larval morphology in relationship to characters preserved in subfossil material. Of particular interest is the mandible and mentum of T. heliomsonyctios which show close resemblance to the tentatively associated larvae of Corynocera oliveri Lindeberg. An overview over Tanytarsus species with “lugens-type” larvae is given and the phylogenetic value of mandibular accessory teeth is briefly discussed.